1996
DOI: 10.1002/pssa.2211570112
|View full text |Cite
|
Sign up to set email alerts
|

Practical usage of a W moderator for slow positron beam production

Abstract: Polycrystalline 10 μm thick W foil has been used as a reflection type moderator for the remission of slow positrons in a high intensity slow positron beam system using a cyclotron which produces various kinds of positron sources. The stability of the moderation efficiency has been reviewed in different annealing conditions and gas environment for the practical usage. The moderation efficiency of W foil (≈2.0 × 10−4) starts to be saturated above an in‐situ annealing temperature of 2100 °C. Gas treatment with O2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Further measurements in this geometry would be useful. We also note that explicitly allowing for different isotopes, in the case of 58 Co (used by Vehanen et al 1983), the efficiency predicted by the 3D model increases by 14% with respect to 22 Na whilst, in the case of 64 Cu (used by Lee et al 1996), it decreases by 15%. Using the present 3D model, we have further investigated the moderation process for meshes by integrating the contributions from thickness (0 to d) to find the transmission efficiency for a mesh of diameter d. This is shown in Figure 3 where it may be seen to be significantly smaller than experiment.…”
Section: The Efficiency Is Approximatelymentioning
confidence: 86%
See 1 more Smart Citation
“…Further measurements in this geometry would be useful. We also note that explicitly allowing for different isotopes, in the case of 58 Co (used by Vehanen et al 1983), the efficiency predicted by the 3D model increases by 14% with respect to 22 Na whilst, in the case of 64 Cu (used by Lee et al 1996), it decreases by 15%. Using the present 3D model, we have further investigated the moderation process for meshes by integrating the contributions from thickness (0 to d) to find the transmission efficiency for a mesh of diameter d. This is shown in Figure 3 where it may be seen to be significantly smaller than experiment.…”
Section: The Efficiency Is Approximatelymentioning
confidence: 86%
“…There are only two experimental data (Vehanen et al 1983 andLee et al 1996) available in this geometry and, as shown in Figure 2, the scatter is so large that it is difficult to draw a firm conclusion from the comparison. Further measurements in this geometry would be useful.…”
Section: The Efficiency Is Approximatelymentioning
confidence: 99%
“…However, attached surface gases do not appear to be a major problem as an efficiency study where the moderator was heated in situ and then exposed to atmosphere showed only a 10% decrease in efficiency for a 1 h exposure and an 18% decrease for a 12 h exposure. Reheating the moderator was shown to restore the initial efficiency (Lee et al 1996). Thus, the general concensus is that losses in efficiency due to physical defects within the moderator bulk and on its surface are far more important than losses due to attached surface gases.…”
Section: Conversion Of Fast Positrons To Slow Positronsmentioning
confidence: 99%
“…There is some evidence that it may only be necessary to heat just the surface region rather than the entire bulk of the moderator (Anwand et al 2013). 'Exotic' methods, such as exposing the moderator to a hydrogen or oxygen environment between heat treatments, have been tried but appear to have no major influence on improving the efficiency (Lee et al 1996). As for chemically etching prior to heating, efficiencies of moderators prepared by this method have been reported (Saito et al 2002, Weng et al 2004, Williams et al 2015.…”
Section: Conversion Of Fast Positrons To Slow Positronsmentioning
confidence: 99%